2016
DOI: 10.1038/ncomms13821
|View full text |Cite
|
Sign up to set email alerts
|

CCT complex restricts neuropathogenic protein aggregation via autophagy

Abstract: Aberrant protein aggregation is controlled by various chaperones, including CCT (chaperonin containing TCP-1)/TCP-1/TRiC. Mutated CCT4/5 subunits cause sensory neuropathy and CCT5 expression is decreased in Alzheimer's disease. Here, we show that CCT integrity is essential for autophagosome degradation in cells or Drosophila and this phenomenon is orchestrated by the actin cytoskeleton. When autophagic flux is reduced by compromise of individual CCT subunits, various disease-relevant autophagy substrates accum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
107
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 115 publications
(111 citation statements)
references
References 72 publications
(127 reference statements)
3
107
1
Order By: Relevance
“…Autophagosomes (yellow) and autolysosomes (red) in primary neurons. The different images show primary neurons from a transgenic mouse model expressing monomeric red fluorescent protein (mRFP)–green fluorescent protein (GFP)–light chain 3 (LC3) . This model allows one to distinguish non‐acidified autophagosomes (red and green=yellow) from acidified autolysosomes (red only), as the GFP fluorescence is more rapidly quenched by the low lysosomal pH.…”
Section: List Of Genes and Diseases Associated With Impaired Autophagmentioning
confidence: 99%
See 2 more Smart Citations
“…Autophagosomes (yellow) and autolysosomes (red) in primary neurons. The different images show primary neurons from a transgenic mouse model expressing monomeric red fluorescent protein (mRFP)–green fluorescent protein (GFP)–light chain 3 (LC3) . This model allows one to distinguish non‐acidified autophagosomes (red and green=yellow) from acidified autolysosomes (red only), as the GFP fluorescence is more rapidly quenched by the low lysosomal pH.…”
Section: List Of Genes and Diseases Associated With Impaired Autophagmentioning
confidence: 99%
“…The CCT complex prevents accumulation of various autophagy substrates primarily by mediating autophagy rather than through its direct chaperone activity preventing aggregation of such proteins. CCT5 promotes autophagosome degradation by regulating lysosome function, as it has been shown that CCT5 disruption reduced the trafficking of lysosomal enzymes and the v‐ATPase to lysosomes, possibly via interactions with cytoskeleton proteins …”
Section: Hereditary Spastic Paraplegiamentioning
confidence: 99%
See 1 more Smart Citation
“…Further CCT5 expression was found to be also decreased in Alzheimer’s disease (85). It is thus important to understand how decreased activity of CCT complex or individual CCT subunit impacts the stabilization and turnover of tau, whose pathogenic species also accumulates in Alzheimer’s disease.…”
Section: Discussionmentioning
confidence: 99%
“…84 Further CCT5 expression was found to be also decreased in Alzheimer's disease. 85 It is thus important to understand how decreased activity of CCT complex or individual CCT subunit impacts the stabilization and turnover of tau, whose pathogenic species also accumulates in AD. Although the physiological implications remain to be defined, our study has established that increased expression of CCT5 had a clear impact on tau-mediated functions such as axonal transport.…”
Section: Discussionmentioning
confidence: 99%